2006
DOI: 10.1093/brain/awh721
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of multiple sclerosis: a geographically based study 9: Observations on the progressive phase of the disease

Abstract: The clinical features of relapses and progression largely define multiple sclerosis phenotypes. A relapsing course is followed by chronic progression in some 80% of cases within 2 decades. The relationship between these phases and long-term outcome remains uncertain. We have analysed these clinical features within a well-studied natural history cohort with mean follow-up of 25 years. For the entire cohort, median times to reach Disability Status Scale (DSS) 6, 8 and 10 were 12.7, 20.6 and 43.9 years, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
313
5
15

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(360 citation statements)
references
References 53 publications
27
313
5
15
Order By: Relevance
“…The fact that relapsingremitting and primary progressive MS have the same allelic frequency of HLA-DRB1*1501 in conjunction with a similar AO, reducing the effect of this allele in both disease forms adds more genetic support to the notion that relapsing-remitting and primary progressive MS are the same disease. Indeed, natural history data have shown similar rates of disability accumulation in both disease forms once they enter the progressive phase; 19 it is merely that progression in relapsing-remitting MS is preceded by transient episodes of disease activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that relapsingremitting and primary progressive MS have the same allelic frequency of HLA-DRB1*1501 in conjunction with a similar AO, reducing the effect of this allele in both disease forms adds more genetic support to the notion that relapsing-remitting and primary progressive MS are the same disease. Indeed, natural history data have shown similar rates of disability accumulation in both disease forms once they enter the progressive phase; 19 it is merely that progression in relapsing-remitting MS is preceded by transient episodes of disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that relapsingremitting and primary progressive MS have the same allelic frequency of HLA-DRB1*1501 in conjunction with a similar AO, reducing the effect of this allele in both disease forms adds more genetic support to the notion that relapsing-remitting and primary progressive MS are the same disease. Indeed, natural history data have shown similar rates of disability accumulation in both disease forms once they enter the progressive phase; 19 it is merely that progression in relapsing-remitting MS is preceded by transient episodes of disease activity.A recent epidemiological study has shown that affected pairs of relatives tend to be more alike for AO based on how closely related they are, with the greatest degree of similarity seen for concordant monozygotic pairs (r¼0.60) and the least for first-cousin pairs (r¼0.10). 20 Dizygotic twins share the same number of genes as do siblings, but show a much stronger AO correlation (r¼0.54 and r¼0.20, respectively).…”
mentioning
confidence: 99%
“…However, development of a progressive disease course and rate of postprogression disability accumulation seems to be age-dependent, and does not correlate with the rate of preprogression disability accumulation. 2,4,[7][8][9][10][11] Although age at progressive disease onset and pace of disability accumulation are similar across MS subtypes (e.g., PPMS vs SPMS), there is a wide range and distribution. This suggests that the presence or absence of other clinical parameters underlies the differences in long-term disability accrual between patients with progressive MS.…”
mentioning
confidence: 99%
“…1 A Organização Mundial da Saúde estima uma prevalên-cia geral de 30 casos de EM por uma população de 100.000 pessoas. 2 Presumindo uma população mundial de 7,4 bilhões, 3 haveria aproximadamente 2,2 milhões de pessoas globalmente com EM.…”
Section: Antecedentesunclassified